(untitled) (Research, Society and Development, 2022)
Therapeutic hypothermia is a technique used after cardiac arrest with the aim of mitigating neurological damage and improving the chances of survival. It is a painstaking process and must be closely monitored in order to avoid complications. The nurse participates in the provision of direct care in the Intensive Care Unit and must be able to intervene in all phases of post-CPA hypothermia induction. Therefore, this study aims to investigate in the literature, the role of nurses in post-CPA therapeutic hypothermia in intensive care units. This is an integrative review of the literature, carried out in the databases Scielo, LILACS, BdEnf and Portal Periódicos Capes, between June and July 2022. The results showed that the nurse has been working since the beginning of TH after CRA and needs to be trained to provide such care. Temperature monitoring, probing and organization of sedation are some of the interventions performed. In this process, nurses have the Nursing Process in order to assist them in the organization of care. Therapeutic hypothermia is a viable, safe and low-cost method for reducing metabolic rate and oxygen consumption in patients after cardiac arrest, and nurses are essential at all stages.